The Influence of the STAD Type Cooperative Learning Model Based on Canva Media on Student Learning Outcomes in the Public Relations and Protocol Management Automation Subject - Pasaribu, Ruspida; Munajat, Munajat (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model assisted by Canva media on the learning outcomes of class XI OTKP students in the Public Relations and Protocol subject at SMK Negeri 1 Dolok Sanggul in the 2024/2025 academic year. This study uses a quantitative approach with a quasi-experimental design. The sample consists of two classes, namely class XI OTKP 2 as the experimental class that applies the STAD model based on Canva media, and class XI OTKP 3 as the control class that uses the STAD model without the aid of media. Data collection was carried out through an initial test (pre-test) and a final test (post-test) to measure student learning outcomes. The results showed that the average post-test score of students in the experimental class was 84.70 with a standard deviation of 6.49, while the control class obtained an average of 76.67. Statistical tests using the Independent Sample t-test and the Mann-Whitney U test produced a significant value.